Relationship between Structure and Dyeing Properties of Disperse Dyes in D5 Medium. (December 2021) - Huang, Jingming; Zhang, Hongjuan; Pei, Liujun; Wang, Jiping
In this paper, two disperse dyes with different substituents were selected to dye polyester fabrics in decmethylcyclopentasiloxane (D5) medium. The structures and dyeing performance of the two dyes were studied and compared. The results showed that dyes with lower solubility in D5 medium had higher dyeing rates. DFT calculations showed that large steric hindrance of cyano groups on diazo components contributed to improving the dyeing rate. This was due to the generation of more monomolecular dyes by destroying π-π stacking interactions. These results provide theoretical guidance for improving the exhaustion and further promote the industrial development of disperse dye in a D5 dyeing system.